P177 What are the real-world outcomes of locally advanced vulval cancer patients who receive neoadjuvant chemotherapy to downstage their disease?. (1st November 2019) - Baillie, K; Crearie, C; Laskey, J; Bennie, M; Sadozye, A; Harrand, R; Burton, K; Siddiqui, N; Reed, N; Graham, K
Abstract : Introduction/Background: Limited studies suggest that locally advanced vulval cancer may be rendered more operable with neoadjuvant chemotherapy (NACT). In the West of Scotland Cancer Network (WoSCAN), NACT is offered to women with sphincter threatening disease. A previous local audit in 2012 reported an operability rate of 35% and median overall survival (OS) of 20 months, following NACT. This study aimed to identify the proportion of patients who proceed to tailored surgery with wide local excision ± groin node dissection following NACT for vulval cancer in the real-world setting. Methodology: Data were collected retrospectively from electronic clinical records of WoSCAN patients who commenced NACT between January 2012 and December 2016. Statistical analysis was performed using R®. OS was estimated using Kaplan-Meier method and Cox's proportional-hazards models used to calculate unadjusted hazard ratios (HR). Results: 57 patients were identified with a median age of 65 years (range 35–88). Cisplatin/Capecitabine was the most common NACT regimen (80.7%); a median of 3 cycles were administered. 43.9% proceeded to surgery, 35.1% received primary (chemo)radiotherapy and 21.2% did not receive any definitive therapy. Exenteration was avoided in all cases. Data were censored in February 2018 at which time 29 patients (50.9%) remained alive and 35.1% required further treatment for relapse. Median OS was 39.3 months. Survival was shorter in patients receiving NACT alone (HR 3.44 (95% CI 1.33–8.87)) but not significantly different between surgery and radiotherapy groups. Conclusion: Over 40% of women received surgical resection with sphincter preservation. Our operability rate has increased and OS is longer than our previous audit, reasons for which are currently being explored. Survival with NACT followed by radical (chemo)radiotherapy was comparable to surgery. Local relapse remains an issue and close follow up is advised as salvage therapy may be indicated. Disclosure: This study was funded by the Scottish Government. The authors declare no competing interests.